PKM PENDAMPINGAN PEMBUATAN PRODUK OLAHAN IKAN PAYUS (BAKSO IKAN PAYUS) DI DESA LINDUK PONTANG SERANG - Ihwan Satria Lesmana; Reza Aditya Dermawan; Yuliana Rahayu; Rahmat Hidayat; Diniyatul Jaliyah; Anisa Nurulaini (Gapenas Publisher, 2022)
One of the verified fishery products that can be developed and has the opportunity to add added value is fish balls. The development of various processed fishery products can be used as an alternative to fostering the habit of consuming fish for the people of Indonesia, as well as an effort to increase the nutritional value of the community. One form of processed fish products is fish balls. Meatballs are processed products from meat that are quite popular with the public. In general, meatballs are made from beef but lately many are found in the market meatballs made from fish meat. Almost all types of fish can be used as ingredients for making meatballs including payus fish with proper processing. Payus fish (Elops hawaiensis) is a pest for whitefish in traditional ponds. This fish is famous as a predator of whitefish fry with a characteristic slimmer body shape compared to whitefish, usually called male milkfish. Payus fish is a very important freshwater fishery commodity in the northern waters of Banten Province